Analisis Minat Siswa Kelas Rendah dan Kelas Tinggi Terhadap Pembelajaran SBdP Sekolah Dasar SD 2 Purwosari - Sya’diah, Khalimatus; putri aji, Nafisa; Wijayanto, Wasis (JPKS (Jurnal Pendidikan dan Kajian Seni), 2025)
This study aims to determine the effect of SBdP learning on the interest of low grade and high grade students at the elementary school level in SBdP learning in the field of art. With the use of qualitative methods descriptive narrative approach, collecting data sources with observation, interviews, and documentation from sources namely homeroom teachers and students of high and low classes of SD 2 Purwosari. The results of the research obtained are the influence of SBdP learning, especially in the field of fine arts on student interest in the field of art. According to the results of interviews that have been carried out, there are differences in the interest of high-class students who are no longer interested in drawing activities. SD 2 Purwosari has developed various extracurricular activities that lead to the field of art, including extra dance, tambourine literature, and extra drawing which is included as one of the lessons that must be followed by all students from grade 1 to grade 6. According to the observation data obtained by the author, there is a difference in the level of student interest, where low-grade students are still enthusiastic about learning the art of drawing while high-grade students already feel bored and monotonous about the drawing and painting learning process.